¿Qué hay de política en la filosofía? : ocho ensayos - Svampa, M. Lucila (María Lucila); Bey, Facundo; Lefort, Claude (Instituto de Investigaciones "Gino Germani" : Consejo Latinoamericano de Ciencias Sociales, 2018)
Few other issues arouse more controversy than that of the links between philosophy and politics: that those who dedicate themselves to philosophy should not be influenced by politics, that if it corresponds to politics to be aided by philosophy, that if philosophical knowledge has to detach oneself from political positions, that if it is convenient for the academic institutions of the humanities to become independent from the power of the day, etc. All these are discussions that we inherited (not without reformulating them and, therefore, re-transforming them) from Antiquity, in which the figure of the philosopher king would already appear at the hand of Plato. This book brings together a variety of approaches that go through debates on factual and value judgments, on democracy as a form of government and on the intervention of history in the link between philosophy and politics. Recovering ancient and modern thought, but concentrating on the work of contemporary intellectuals, the authors set in motion elucidations by greats such as Max Weber, Jacques Rancière, Louis Althusser, Philippe Lacoue-Labarthe and Leo Strauss, among others. Thus, they offer here a vivid panorama of the controversies that inhabit the intersections between philosophy and politics, crowning the volume with the translation of a text by Claude Lefort, hitherto unpublished in Spanish.